PERAN KOMUNIKASI PENYULUHAN DALAM PENERAPAN TEKNOLOGI USAHATANI DI KECAMATAN LANGOWAN BARAT - Clara F. Mongisidi; Lyndon R. J. Pangemanan; Rine ., Kaunang (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the role of communication extension counselor and how far farmers can understand the purpose and purpose of counseling. This research was conducted by using primary data obtained from direct interview with Field Extension Officer and Farmer Group using the prepared kusioner. Secondary data obtained from BPS Manado City and BP3K Office. The result of the research shows that the communication done by PPL has used good communication technique so that the farmer group following the counseling can receive and understand the intent and purpose of the material which have been submitted by each PPL.